A process of students and their instructor developing a final closed-book mathematics exam. Issue 1 (2nd January 2016) - Rapke, Tina
ABSTRACT: This article describes a study, from a Canadian technical institute's upgrading mathematics course, where students played a role in developing the final closed-book exam that they sat. The study involved a process where students developed practice exams and solutions keys, students sat each other's practice exams, students evaluated classmates' solutions to the practice exams, and finally the instructor used questions from the practice exams to develop the 'live' final exam. Phenomenography is used to analyse interview data and report students' experiences. Through the results, claims are made that students experienced deep approaches to learning and worked as partners in learning, teaching and assessment during the process of developing the final exam with their instructor.